Sandwich Generation in Contemporary Indonesia: Determining Responsibility in Caring for Elderly under Islamic Law and Positive Law - Syufa'at, Syufa'at; Zaidi, Syed Muhammad Saad; Mutholaah, Mutholaah (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
The emergence of the term sandwich generation is believed to be a phenomenon that is common in Indonesian society. What's more, the number of baby boomers has become a concern both from a social and economic perspective for the generations below them. Therefore, many dilemmas arise regarding how the Indonesian people respond to sandwich generation, whether this position is a burden or a gift for the perpetrators of sandwich generation. This paper will later answer how the history of the emergence of the term sandwich generation and its development in Indonesia and the perception of sandwich generation on Islamic law perspective. This study uses a qualitative method by collecting library data sourced from related books and journals so as to produce a discussion where the term sandwich generation is a generation that directly supports the generation above and below (the other two generations). The current sandwich generation has actually existed for a long time, even in the era of Prophet Muhammad SAW. The concept of sandwich generation can be interpreted the same as the concept of birrul walidain or devoted to parents. Of course, the concept of birrul walidain is a practice that is highly recommended to be done for every Muslim.